European capital markets: Competition between systems - Colin Mayer (EIB Papers, 1999)
There is an active global debate on corporate governance. A few years ago, there was serious concern about whether US companies would be able to compete against the powerful corporate groupings supported by closely involved banks in the Far East. Now, following the collapse of the East Asian economies, and in particular Japan, 'shareholder value' oriented companies, operating in the stock market-dominated financial system of the US, are increasingly seen to be enjoying a competitive advantage over their foreign rivals. The corporate and financial systems of the Far East are currently believed to have resulted in serious misallocation of resources, while US companies and institutions have backed high tech, fast growth industries. In Europe, the main contrast is between UK and Continental European financial markets. Until recently, there was considerable concern that UK companies were disadvantaged by a preoccupation with short-term returns for shareholders while Continental European companies could enjoy longer term support from their banks and corporate allies. Now, the prevailing view is that Continental systems will have to adapt to market-oriented conditions and that lack of transparency, illiquidity of shares and poorly functioning financial markets have impeded the growth and restructuring of European industry. This is most clearly reflected in the immature state of the European venture capital industry. While the UK and US financial systems were until recently regarded as being seriously deficient in promoting corporate activity, they are now viewed as being in the vanguard of corporate development. This article will argue that this debate will bear crucially on the way in which financial markets will develop in Europe.
Keywords: 330; Europäische Wirtschafts- und Währungsunion; Finanzmarkt; Wettbewerb; Deutschland; Frankreich; Großbritannien